2008
DOI: 10.1007/s11682-008-9051-2
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Tensor Imaging in Preclinical Huntington’s Disease

Abstract: Diffusion tensor imaging was used to study brain related changes in white matter that may be associated with Huntington's Disease progression. Thirty-one preclinical gene-mutation carriers were imaged cross-sectionally using diffusion tensor and anatomical brain imaging. Subjects were individuals who had a known gene mutation for HD but did not manifest motor diagnostic criteria for HD. Fractional anisotropy scalar maps showed a positive correlation with five year probability of diagnosis (based upon gene repe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 26 publications
2
42
0
Order By: Relevance
“…However, the increase in RD was emphatic enough to lead to a decrease in FA. Our finding of altered CST WM is in line with the findings of previous WM DTI studies on Pre-HD subjects (Rosas et al 2006;Magnotta et al 2009;Stoffers et al 2010). Nevertheless, although these studies were valuable, they provided only a limited assessment of the CST because they used a whole brain or region of interest approach, with limited DTI parameters.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, the increase in RD was emphatic enough to lead to a decrease in FA. Our finding of altered CST WM is in line with the findings of previous WM DTI studies on Pre-HD subjects (Rosas et al 2006;Magnotta et al 2009;Stoffers et al 2010). Nevertheless, although these studies were valuable, they provided only a limited assessment of the CST because they used a whole brain or region of interest approach, with limited DTI parameters.…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, these previous macro-and microstructural studies focused on wholebrain WM or Region of Interest analyses. Only a few studies investigated a specific tract in its entirety, for example, the whole commissural fiber (Magnotta et al 2009;Muller et al 2011;Di Paola et al 2012;Dumas et al 2012), the motor corticostriatal circuit (Kloppel et al 2008;Bohanna, Georgiou-Karistianis, Sritharan et al 2011) or the WM pathway of the sensorimotor cortex (Dumas et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is relatively small as compared to the variation that we have seen in subjects with prodromal HD. In a prior study, we found that the FA value change was *0.1 across the 5-year probability of onset (Magnotta et al, 2009). The CV is relatively small compared to this.…”
Section: Discussionmentioning
confidence: 88%
“…We anticipated differences on the basis of previous reports on white matter integrity loss in premanifest HD using DTI. 7,8,31 DTI can be used to examine protons in free water and their diffusive properties in more than 1 way, namely, the strength of the directional of diffusivity (fractional anisotropy), the average amount of diffusivity (mean diffusivity), and also the amount of diffusivity in either the radial and axial direction. DTI has the potential for examining and quantifying many features of brain tissue, all captured by the terms structural integrity and/or organization.…”
Section: Figmentioning
confidence: 99%